Introduction to reflectance confocal microscopy and its use in clinical practice - Levine, Amanda; Markowitz, Orit (JAAD Case Reports, 2018)
Reflectance confocal microscopy (RCM) is a novel technology that provides noninvasive, in vivo imaging of the skin at nearly histologic resolution. In 2016, the US Centers for Medicare and Medicaid Services (CMS) established reimbursement codes for RCM image acquisition and for the reading and interpretation of images. The combination of RCM imaging with dermoscopy has improved the accuracy of skin cancer diagnosis while reducing the number of biopsies of benign skin lesions. With that, we are starting to see more dermatologists and dermatopathologists using RCM in clinical practice. This editorial is to serve as an introduction on RCM imaging with a focus on its usefulness in both the diagnosis and management of skin cancers. We end by briefly describing the characteristic RCM features of normal skin to serve as a building block for later cases that will explore both the benefits and drawbacks of incorporating RCM imaging for benign and malignant lesions.